2021
DOI: 10.3390/app11052160
|View full text |Cite
|
Sign up to set email alerts
|

Sea Bass Side Streams Valorization Assisted by Ultrasound. LC-MS/MS-IT Determination of Mycotoxins and Evaluation of Protein Yield, Molecular Size Distribution and Antioxidant Recovery

Abstract: Sea bass side streams obtained from the fish industry can be a good source of nutrients such as high-quality protein, lipids, and antioxidants. In this context, it is interesting to develop innovative approaches to extract the added-value compounds from fish side streams. In this study, a strategy to obtain valuable compounds and to minimize the presence of toxins from fish side streams assisted by ultrasound technology is presented. For this purpose, ultrasound-assisted extraction (UAE) conditions have been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The results showed that compared with traditional methods, ultrasound-assisted acid/alkaline isoelectric solubilization precipitation can significantly increase the protein recovery rate from 50-64% to 94%. Similarly, Al-Khawli et al [25] also used ultrasound to assist the extraction of protein from the sea bass side stream. Under ultrasound-assisted treatment, the protein content of the fish side stream extracts was significantly increased, with the highest modifications observed for the viscera samples.…”
Section: Protein Contentmentioning
confidence: 99%
“…The results showed that compared with traditional methods, ultrasound-assisted acid/alkaline isoelectric solubilization precipitation can significantly increase the protein recovery rate from 50-64% to 94%. Similarly, Al-Khawli et al [25] also used ultrasound to assist the extraction of protein from the sea bass side stream. Under ultrasound-assisted treatment, the protein content of the fish side stream extracts was significantly increased, with the highest modifications observed for the viscera samples.…”
Section: Protein Contentmentioning
confidence: 99%
“…The total protein content of the obtained extracts was determined as described by Al Khawli et al [14].…”
Section: Proteins 271 Total Protein Contentmentioning
confidence: 99%
“…On the other hand, other techniques have been used for the valorization of sea bass ide streams, obtaining extracts with antioxidant capacity through the application of ultrasoundassisted extraction (UAE) [14] and pressurized liquid extraction (PLE) [15]. Specifically, studies on nutritional value have been carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Knobloch et al [5] found that the surface microbial community of sea bass could be influenced by close-proximity and continuous ultrasound treatment. The US has an antimicrobial effect on Staphylococcus aureus [6] , Pseudomonas fluorescens [7] , Listeria monocytogenes and other pathogens [8] , which was mainly due to the destruction of cell structure and integrity by ultrasonic cavitation leading to microbial apoptosis [9] , [10] . The recent researches showed that ultrasound in combination with SAEW and other physical processing methods could reduce the number of bacteria efficiently [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%